COATING OF ORANGE FRUIT WITH NANO-SILVER PARTICLES TO MINIMIZING HARMFUL ENVIRONMENTAL POLLUTION BY CHEMICAL FUNGICIDE - & et al., Khaleel (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to investigate the coating of nanoparticles to minimizing harmful of chemical fungicide in fruit industrial sector. The Effects of coating fruit surface with different concentrations of Nano-silver on the development of mycelium growth of, Penicillium digitatum and Aspergillus niger during storage were estimated. Coated treatments with silver recorded fully reduction of the fungal growth (100%,) on surface of fruit with concentration of 50 ppm and 100 ppm as compared with uncoated samples and fungicide. Also, the treatment with 100ppm of silver showed a significant decrease in weight loss compared with uncoated fruit. Application of nanotechnology can be an important way to replacing chemical fungicides in agricultural sector in future with regard controlling fungal post-harvest rot in stored fresh fruit.